Antibacterial and anticorrosion behavior of bioactive complexes of selected transition metal ions with new 2‐acetylpyridine Schiff base. (11th January 2022) - Deghadi, Reem G.; Elsharkawy, Ahmed E.; Ashmawy, Ashraf M.; Mohamed, Gehad G.
Abstract: Successful preparation of Schiff base 4‐(4‐aminophenoxy)‐ N ‐(1‐(pyridin‐2‐yl)ethylidene)aniline derived from refluxing of 4, 4‐oxydianniline with 2‐acetylpyridine within 2 h in 1:1 molar ratio was performed. Different transition metal complexes were synthesized by reacting metal chlorides with the formed ligand in 1:1 molar ratio. Structural features of the complexes were obtained from different tools such as infrared (IR), 1 H‐nuclear magnetic resonance ( 1 H‐NMR), ultraviolet–visible (UV‐vis), molar conductivity, thermogravimetric (TG)/differential thermogravimetric (DTG), microanalysis, and mass spectrometry. All complexes had an octahedral structure and Schiff base acted as a neutral bidentate ligand that linked to metal centers via N ‐azomethine and N ‐pyridine atoms. Cr(III), Fe(III), and Ni(II) complexes were electrolytes while other complexes were nonelectrolytes. The molecular structure of Schiff base was optimized theoretically and its HOMO and LUMO energies were dictated by B3LYP/DFT calculations. The in vitro antibacterial activity versus some selected bacteria species showed that all prepared compounds were biologically active except Fe(III) complex against certain species and Co(II) complex had the highest biological activity values. Molecular docking was used to determine effective binding modes between ligand and its [Co(L)(H2 O)2 Cl2 ]·4H2 O complex with active sites of 4WJ3, 4ME7, 4K3V, and 3T88 receptors. The strongest binding of Co(II) complex was with the 4ME7 receptor with lowest binding energy value −25.4 kcal mol −1 . Schiff base as corrosion inhibitors for mild steel in 1.0‐M HCl had been investigated using electrochemical impedance spectroscopy (EIS), potentiodynamic polarization (PP), and electrochemical frequency modulation (EFM). The results showed that the inhibitor acts as a mixed‐type inhibitor. The inhibition efficiency increases with increasing inhibitor concentration to its maximum of 97.5% at 1 × 10 −3  M solution. The adsorption model obeys the Langmuir isotherm, and Gibbs free energy was around −40 kJ/mol, indicating that it is spontaneously and chemically adsorbed on the surface. SEM/EDX results proved the sticking of a barrier film on the mild steel sample. Abstract :